Peningkatan Kinerja Karyawan pada Badan Usaha Milik Desa Kota Pari dengan Edukasi Kompetensi Kerja - Juniarti, Juniarti; Pohan, Syahrial Hasanuddin; Waruwu, Ahmad Aswan (MARHALADO: Jurnal Pengabdian kepada Masyarakat, 2026)
Kota Pari Village, Pantai Cermin Sub-district, Serdang Bedagai Regency, holds promising tourism potential; however, this potential has not been optimally utilized due to a number of issues faced by the residents, such as low work competence, limited access to information on business development management training, residents' insufficient responsiveness to changes in the management system of the village-owned enterprise, and low willingness among residents to apply the knowledge provided, which frequently leads to disagreements during work competence training activities. Therefore, this community service program aims to identify these issues and provide appropriate solutions for the residents of Kota Pari Village and its surrounding areas. Through this program, it is expected that residents will be able to apply work competence to improve employee performance within the Village-Owned Enterprise, actively engage in business development management through creative craftsmanship, and make this a cornerstone for improving their standard of living and economic welfare, with support and facilitation from the Kota Pari Village Office, Pantai Cermin Sub-district, Serdang Bedagai Regency.